Dopamine Increases a Value-Independent Gambling Propensity - Rigoli, Francesco; Rutledge, Robb B; Chew, Benjamin; Ousdal, Olga T; Dayan, Peter; Dolan, Raymond J (Neuropsychopharmacology (New York, N.Y.), 2016)
Although the impact of dopamine on reward learning is well documented, its influence on other aspects of behavior remains the subject of much ongoing work. Dopaminergic drugs are known to increase risk-taking behavior, but the underlying mechanisms for this effect are not clear. We probed dopamine's role by examining the effect of its precursor L-DOPA on the choices of healthy human participants in an experimental paradigm that allowed particular components of risk to be distinguished. We show that choice behavior depended on a baseline (ie, value-independent) gambling propensity, a gambling preference scaling with the amount/variance, and a value normalization factor. Boosting dopamine levels specifically increased just the value-independent baseline gambling propensity, leaving the other components unaffected. Our results indicate that the influence of dopamine on choice behavior involves a specific modulation of the attractiveness of risky options-a finding with implications for understanding a range of reward-related psychopathologies including addiction.